Malignant Fibrous Histiocytoma, Aggressive Fibromatosis and Benign Fibrous Tumors Express mRNA for the Metalloproteinase Inducer EMMPRIN and the Metalloproteinases MMP-2 and MT1-MMP. (2001) - Åhlén, Jan; Enberg, Ulla; Larsson, Catharina; Larsson, Olle; Frisk, Tony; Brosjö, Otte; Rosen, Anette von; Bäckdahl, Martin
Abstract : Purpose: Extracellular matrix metalloproteinase inducer (EMMPRIN) has been shown to stimulate fibroblasts to production of matrix metalloproteinases (MMPs). MMPs comprise a family of proteolytic enzymes implicated in the degradation of extracellular matrix which has been proposed to be one of the essential steps in tumor invasion and metastases. In the present study we investigated the expression and location of mRNAs for EMMPRIN, matrix metalloproteinase-2 ( MMP-2 ), and membrane-type 1 matrix metalloproteinase ( MT1-MMP ) in mesenchymal tumors with different tendencies to recur or metastasize. Subjects: Eight malignant fibrous histiocytomas (MFH), seven aggressive fibromatosis (AF), and six benign fibrous tumors (BF). Method: The mRNA-expression of EMMPRIN, MMP-2 and MT1-MMP were studied using mRNA in situ hybridization technique. Results: The mRNA-expression of EMMPRIN, MMP-2 and MT1-MMP respectively were found at varying frequency and level in all tumor types. The mRNAs corresponding to EMMPRIN and MMP-2 were seen in neoplastic cells as well as in endothelial cells both inside and outside the tumor pseudo-capsule, whereas MT1-MMP was seen only within the tumors. The estimated mRNA levels of EMMPRIN and MMP-2 covariated significantly. Overall, the highest expression was found in the MFH tumors and the lowest levels in the BF tumors. Discussion: These findings suggest that the MMP-inducer EMMPRIN and the extracellular matrix degrading system involving the metalloproteinases MMP-2 and MT1-MMP is frequently activated in mesenchymal tumors. The covariation between EMMPRIN and MMP-2 support previous findings that EMMPRIN may be an inducer of MMP-2. The high levels of MMP-2 mRNA in MFH indicate a relationship between the proteolytic activity of MMP-2 and the tumor aggressiveness.